From traditional to constructive digital classrooms: Learners’ perceptions of technologies in reading classes - Khalaf, Bilal Khalid; Al-Abbas , Linda S.; Mahmood , Ihab Majeed; Shabeeb , Taha Ibrahim; Mustafa , Sajjad Abdulmunem (Research Journal in Advanced Humanities, 2025)
Technologies had significantly contributed to developing academia, especially for academic literacies. The growing demand for understanding the integration between contemporary reading technologies’ usefulness, ease of use, continuous use and learners’ perceptions in a higher education context is highlighted in the literature. Among frequent studies on implications of reading technologies, only a few came across issues concerning learners’ perceptions; none of them was conducted in an Arab context. The present study aims to explore learners’ perceptions of implications, i.e., usability and usefulness, of technologies in traditional reading classrooms. Furthermore, the study aims to explore their preferences and motivations to continue using technologies in performing future academic tasks. A quantitative survey questionnaire is used to collect data from 351 respondents through 34 questions using the Technology Acceptance Model (TAM) at 24 universities. The data were analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM), as well as descriptive analysis using SPSS.25. The study verified proposed correlations in the conceptual model. The model and proposed hypotheses yield novel findings. The study identified preferences for using smartphones, then computers, interactive whiteboards and digital platforms in reading classes, respectively. It also found that the usefulness of technology significantly influences learners’ preferences and ability to use it. The findings displayed a total variance of 89% for learners’ motivation to continue using technologies, which they are able to use in future academic tasks. The study concluded with implications and recommendations for researchers and policymakers.